2017
DOI: 10.1017/jfm.2017.466
|View full text |Cite
|
Sign up to set email alerts
|

Stability and sensitivity of a cross-flow-dominated Falkner–Skan–Cooke boundary layer with discrete surface roughness

Abstract: Stability and sensitivity of a crossflow-dominated Falkner-Skan-Cooke boundary layer with discrete surface roughness. Journal of Fluid MechanicsAccess to the published version may require subscription. N.B. When citing this work, cite the original published paper. With the motivation of determining the critical roughness size, a global stability and sensitivity analysis of a three-dimensional Falkner-Skan-Cooke (FSC) boundary layer with a cylindrical surface roughness is performed. The roughness size is chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
(49 reference statements)
3
23
2
Order By: Relevance
“…(2009 b ) and Brynjell-Rahkola et al. (2017) etc. The eigenvalue estimation is done using the implicitly restarted Arnoldi method (Sorensen 1992) implemented in the open source software package ARPACK (Lehoucq, Sorensen & Yang 1998).…”
Section: Linear Instability Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2009 b ) and Brynjell-Rahkola et al. (2017) etc. The eigenvalue estimation is done using the implicitly restarted Arnoldi method (Sorensen 1992) implemented in the open source software package ARPACK (Lehoucq, Sorensen & Yang 1998).…”
Section: Linear Instability Resultsmentioning
confidence: 97%
“…The system is solved by estimating the eigenvalues of the time-stepping operator. The method was first used by Eriksson & Rizzi (1985) and has been used in several previous works by Barkley, Gomes & Henderson (2002), Bagheri et al (2009b) and Brynjell-Rahkola et al (2017) etc. The eigenvalue estimation is done using the implicitly restarted Arnoldi method (Sorensen 1992) implemented in the open source software package ARPACK (Lehoucq, Sorensen & Yang 1998).…”
Section: Oscillating Cylinder At Subcritical Reynolds Numbersmentioning
confidence: 99%
“…However, as established by several studies [9,10,81,82], global stability analysis is only able to provide an estimation for the upper bound of the transition diagram based on several literature results reported in Ref. [33], whereas a clear understanding of the physical mechanisms governing subcritical transition, allowing a prediction of the lower bound of the transition diagram, is still lacking.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The secondary instability causing the breakdown in the flow over their wing thus indicates a convective nature. Brynjell-Rahkola et al (2017) show that in the three-dimensional Falkner-Skan-Cook boundary layer the wake of a large roughness can change into an oscillator driving a secondary instability such that the flow becomes globally unstable. They found that the first mode that becomes unstable in their simulations is the 'z'-mode.…”
Section: Introductionmentioning
confidence: 96%